2008
DOI: 10.1038/oby.2007.101
|View full text |Cite
|
Sign up to set email alerts
|

Grazing and Loss of Control Related to Eating: Two High‐risk Factors Following Bariatric Surgery

Abstract: background: Gastric restrictive surgery induces a marked change in eating behavior. However, the relationship between preoperative and postoperative eating behavior and weight loss outcome has received limited attention. objective: This study assessed a range of eating behaviors before and 1 year after laparoscopic adjustable gastric banding (LAGB) and explored the nature and extent of change in eating patterns, their clinical associates, and impact on weight loss. Methods and Procedures: A 12-month observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
338
4
28

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(381 citation statements)
references
References 50 publications
11
338
4
28
Order By: Relevance
“…Latner & Wilson, 2002). In addition, studies have reported that BE behaviours can continue or develop postoperatively affecting weight loss outcome (Hsu, Betancourt & Sullivan,1996;Scholtz, Bidlake, Morgan, Fiennes, El-Etar, & Lacey, 2007) whereas others report a decrease or disappearance following surgery (Powers et al, 1999;White et al, 2006;Colles, Dixon, & O'Brien, 2008). Such conflictions may be the result of methodological issues such as poor study design, measurement error or sampling errors due to problems with sample sizes or may indicate that the role of eating behaviours in individuals undergoing obesity surgery is more complex than first thought.…”
Section: Introductionmentioning
confidence: 99%
“…Latner & Wilson, 2002). In addition, studies have reported that BE behaviours can continue or develop postoperatively affecting weight loss outcome (Hsu, Betancourt & Sullivan,1996;Scholtz, Bidlake, Morgan, Fiennes, El-Etar, & Lacey, 2007) whereas others report a decrease or disappearance following surgery (Powers et al, 1999;White et al, 2006;Colles, Dixon, & O'Brien, 2008). Such conflictions may be the result of methodological issues such as poor study design, measurement error or sampling errors due to problems with sample sizes or may indicate that the role of eating behaviours in individuals undergoing obesity surgery is more complex than first thought.…”
Section: Introductionmentioning
confidence: 99%
“…Não há consenso na literatura e dados precisos que garantam bom ou mau prognóstico adequadamente estudados e comprovados 14,25 . Os critérios de TCAP e episódios compulsivos precisam ser revisados e ampliados para que se obtenha mais precisão nas pesquisas e diagnósticos deste distúrbio 11 . Clareza na definição de comportamentos alimentares inadequados após opeação, métodos confiáveis para identificá-los e estratégias de intervenção pós-operatória são necessários para otimizar os resultados de perda de peso e promover o bem-estar psicológico dos pacientes.…”
Section: Discussionunclassified
“…These finding are consistent with other WLS studies that report, in most cases of recidivism, weight loss failure is due to dietary noncompliance or an inability to change eating and exercise behaviors. [17][18][19][20][21][22] Findings from the Swedish Obesity Subjects study reported that baseline caloric intake was 2,800 calories. 35 At 6 months postsurgery, the study reported caloric intake at approximately 1,500 calories, and by 10 years postsurgery, the calorie intake had increased to an average of 1,800-2,000 calories per day.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20]41,42 The study participants expressed in great detail their personal struggles with healthy food choices, managing stress, family and work environment support, and their overall perception of WLS outcomes. More education on food choices and more emotional support from family members, co-workers, support groups, and the medical community were identified as perceived needs to maintain weight and to prevent further weight gain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation